APLIKASI PEMBELAJARAN MATEMATIKA INTERAKTIF BERBASIS MULTIMEDIA TINGKAT PENDIDIKAN SEKOLAH DASAR KELAS I (SATU) - Ali Subhan Afrizal (Politeknik Sekayu, 2015)
Learning mathematic is the way for facilitating pushing and supporting the students in studying mathematic. But there are many students at school, especially elementary school do not like mathematic. They think mathematic is the hardest lesson. The opinion make them laziness to study mathematic. So that we need an application in learning interactive mathematic based on multimedia that show animation and interactive simulation to make easy and improve to interesting of students in comprehending mathematic. The application will show animation and simulation from material and every material have fifteen questions. The application is built with program action script 2.0 its used software Adobe flash professional CS6 as animated maker, Adobe photoshop CS5 as graphic processor and Audio editor master as audio processor. The application is created in Compact Disk (CD) interactive with file size 191 MB.